Too far to go to work? Examining the effect of changes in commute time on regional unemployment - Aleš Franc; Soňa Kukučková; Marek Litzman (Ekonomický Časopis)
Commute duration significantly influences decision-making in the labour market, especially for job seekers. This article aims to evaluate the effect of improvements in infrastructure on regional unemployment. Utilizing a unique database comprising commuting time data from all Czech municipalities (n=6241) to their respective regional centres, we identified 1534 changes. Our findings indicate that a one-minute reduction in commuting time to the regional centre is associated with a 0.07 percentage point decrease in the unemployment rate one year later and a 0.19 percentage point decrease after five years. These results suggest that investing in local infrastructure has the potential to mitigate disparities in regional unemployment rates.